0.6(b-4)=-9

Simple and best practice solution for 0.6(b-4)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6(b-4)=-9 equation:


Simplifying
0.6(b + -4) = -9

Reorder the terms:
0.6(-4 + b) = -9
(-4 * 0.6 + b * 0.6) = -9
(-2.4 + 0.6b) = -9

Solving
-2.4 + 0.6b = -9

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2.4' to each side of the equation.
-2.4 + 2.4 + 0.6b = -9 + 2.4

Combine like terms: -2.4 + 2.4 = 0.0
0.0 + 0.6b = -9 + 2.4
0.6b = -9 + 2.4

Combine like terms: -9 + 2.4 = -6.6
0.6b = -6.6

Divide each side by '0.6'.
b = -11

Simplifying
b = -11

See similar equations:

| 8x-2y=41 | | 1.82= | | x(x+12)=(x-4)(x-4) | | ln(5x)+ln(10x)=4 | | 4-v=265 | | 6x+9y=65 | | Y-4+7y=24 | | -16=-4+4y | | y-7.2=9 | | 8x-(11x-9)=24-3x | | X-17=3Y-17 | | a+5=6a | | 75+2y=42 | | 3v=v+38 | | 40.00+19.25x=69.25+16.00x | | ln(7)+ln(x+3)=0 | | y=2x-(-3) | | 9cot^2-3=0 | | 5(3n+1)=7(4n+5)+5 | | 5/3y--10 | | 5(3g+4h)= | | cos(30x)=x/8 | | -10.1q=-80.1-1.2q | | x-30=-4x+15 | | 5pints=liter | | x-30=4x+15 | | 9a(ab+3)(3ab-2)= | | x^(3/4)-x^(1/4) | | 3y-3+y=22+2y-3y | | 2(3x+4)-5=6x+3 | | 7-7q=-15+-15q | | 2=3u+8 |

Equations solver categories